Analisis Lindung Nilai Dengan Menggunakan Swap Dan Forward Untuk Mengurangi Resiko Transaction Eksposure - ., Farhana; Puspitasari, Ratih (LPPM Institut Bisnis dan Informatika Kesatuan, 2017)
Hedging is the one of activities is performed by a company or a bank to protect their business from the risk of changes caused by exchange rates or exchange rate fluctuations. There are some things that should be considered by companies whom often perform the transactions related to interest rate and exchange rate. For example, banks should monitor the company performance against losses caused by foreign exchange and also arrange the strategy, because it is necessary for the company to perform hedging. The research is purposed to learn how to minimize the risks of losses experienced by banks due to hedging techniques usage. The hedging techniques performed are swap and forward hedging. The method used in this study correlation coefficient and simple regression to determine the relationship between the variables in question. The result of this research shows that hedging technique in the buying and selling transactions of foreign exchange has more benefit rather than not. It can avoid the risks of transaction exposures. It can be seen from the significant level, Forward has the significant level in the amount of 0,000. It means the Forward Hedging Technique has an effect to the transaction exposure and Hedging transaction using Swap has the benefit rather than not. The significant level in the amount of 0,007 is smaller than 0,05. It means that Swap Hedging Technique has an effect to the transaction exposure. Accordingly, Forward and Swap deserve to be considered by companies or banks to avoid the risks of transaction exposures.